2018
DOI: 10.1016/j.currproblcancer.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 correlates with the expression of carboxypeptidase B2 and lymphovascular invasion in inflammatory breast cancer: The potential role of tumor infiltrated macrophages

Abstract: Pro-carboxypeptidase B2 (pro-CPB2) or thrombin-activatable fibrinolysis inhibitor (TAFI) is a glycoprotein encoded by the CPB2 gene and deregulated in several cancer types, including breast cancer. Thrombin binding to thrombomodulin (TM), encoded by THBD, is important for TAFI activation. CPB2 gene expression is influenced by genetic polymorphism and cytokines such as interleukin 10 (IL-10). Our previous results showed that tumor infiltrating monocytes/macrophages (CD14/CD16) isolated from inflammatory breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…However, details about signaling and intercellular interaction require further investigation. Mohamed reported that IL10 secreted by tumor-infiltrating monocytes/macrophages (CD14+/CD16+) separated from inflammatory breast cancer patients positively correlated with the expression level of CPB2 , which was crucial to lymphovascular invasion in inflammatory breast cancer 26. However, further studies are required to clarify the role of IL10 in seminoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, details about signaling and intercellular interaction require further investigation. Mohamed reported that IL10 secreted by tumor-infiltrating monocytes/macrophages (CD14+/CD16+) separated from inflammatory breast cancer patients positively correlated with the expression level of CPB2 , which was crucial to lymphovascular invasion in inflammatory breast cancer 26. However, further studies are required to clarify the role of IL10 in seminoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies found higher IL10 levels in metastatic lymph nodes and IL10 polymorphisms associated with increased expression in patients with lymph node-positive breast cancer (107,108). Interestingly, high IL10 levels were also found in inflammatory breast cancer, a particularly aggressive and highly metastatic form of breast cancer, in which this cytokine correlates with the presence of lymphovascular invasion (109). This parameter has been recently associated with an increased risk of BCRL in patients with left side localization.…”
Section: Biological Characteristics Of the Primary Tumorsmentioning
confidence: 99%
“…In three relevant articles, we could not extract the data we wanted. [42][43][44] Second, the sample sizes in some subgroups were small. Third, there were inconsistencies in the types of controls across studies.…”
Section: Strengths and Limitationsmentioning
confidence: 99%